Employees' career orientations and organization career development system :a case study of public and private sector organizations in Sarawak - Norliah, Abdul Aziz (1999)
The main purpose of this study is to determine employees perception towards career development system (CDS) in a public and private organization and the distribution of career orientations among employees in both organizations. This study was conducted in two organizations in Kuching, Sarawak - Dewan Bandaraya Kuching Utara or DBKU (a public organization) and Syarikat Telekom Malaysia Berhad or TELEKOM (a private organization). A total of 180 employees were selected as the sample of the study; 68 employees from DBKU and 112 employees from TELEKOM. This study employed a survey methodology to examine the relationship between the independent variables (selected demographic characteristics, career orientations and associated factors of career development training and development opportunities, supervisor/manager's role in care development and organization reward system) and the dependent variable (career development system).